HUMAN CAPITAL AND HOUSEHOLD FOOD SECURITY IN NORTHERN NIGERIA - Abba, Falmata Baba (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
A major policy area in Nigeria that could result in the attainment of food security as one of the objectives of the sustainable development goals (SDGs) is improvement in the quality of the human capital through education particularly in the Northern Nigeria as the extent of human capital development determines productivity and earnings of household which could further result in the enhancement of household food security. In view of this, the study has examined the relationship between human capital and household food security and has as well ascertained the determinants of household food security in Northern Nigeria using food consumption scores measure of food security. The data employed covers the 3rd round of the general household survey (GHS) (4th wave) conducted in 2018 and produced in 2019. The key issues addressed are the issues of household food security which was measured using food consumption score (FCS) that measures nutritional quality. A total of 4926 households were interviewed, across 519 enumeration areas (EAS). The study employed both descriptive and inferential analytical techniques for data presentation and analyses. The descriptive statistics revealed that the North Central and North West zones are more food secured than the North East. The inferential statistics using multiple regressions (OLS) has revealed that human capital is relevant to food security in the Northern region as it increases personal earnings that improve nutrition and productivity. The other socioeconomic factors that positively influence food security in terms of nutritional quality are access to employment, size and being married while age, dependency ratio and gender showed no significant influence. However, households in the rural areas are more likely to consume foods with low nutritional quality compared to those in the urban areas. Therefore, the study recommends that policy makers should continue to promote the development of education and skill acquisition with the aim to increase food security.